PROJECTS OF CHILDREN’S AND YOUTH PUBLIC ORGANIZATIONS IN THE CONTEXT OF YOUTH POLICY OF UKRAINE - Kharchenko, Nataliia (Theoretical and Methodical Problems of Children and Youth Education, 2021)
Children’s and youth public organizations are an effective partner of the state in the education of children and youth. One of the aspects of the activity of such organizations is the implementation of projects in the framework of the tasks of state target, regional and local programs in the field of youth policy. The purpose of the article is to analyze the competitive bids (programs, projects, activities) developed by civil society institutions, in particular children’s and youth organizations, for the implementation (implementation) of which financial support is provided by the state. The main objectives of the article are: review of regulatory and legal support for the activities of youth and children’s NGOs and the procedure for organizing a competition to determine programs (projects, activities) developed by civil society institutions; analysis of trends in the participation of public organizations, in particular in a pandemic; analysis of tender proposals by priorities of activity. The reasons for the decrease in the number of youth and children’s public organizations participating in the competition are analyzed. Among the main reasons are the following: quarantine restrictions imposed in connection with the pandemic, which made it impossible for traditional activities of public organizations (in particular, holding camps, meetings, talks, etc.); lack of experience in such competitions; unpreparedness of the necessary tender documentation – a set of documents that contain requirements for the preparation of tender proposals by civil society institutions; non-compliance of organizations with one or more criteria required for participation in the competition; lack of staff (adult leaders) who are ready to take on not only educational and organizational functions but also project management (preparation of documentation, budgeting, etc.); availability of other sources of funding, etc. The article emphasizes the need to establish effective cooperation between the state and children’s and youth NGOs as important partners for the development of civil society institutions.